Answer:
g(f(x)) = 6x^2 + 8x - 25
Explanation:
So, first we have to substitute f(x) into the place of x in the g(x). This will be shown as g(f(x)) (which is what we need to solve). Next, we have to substitute 3x^2 + 4x - 7 into the place of x in 2x - 11. We do this because we had to substitute f(x) into the place of x in g(x).
So this is how your equation should look, and then solve:
g(f(x)) = 2(3x^2 + 4x - 7) - 11
g(f(x)) = 6x^2 + 8x - 14 - 11
g(f(x)) = 6x^2 + 8x - 25 < ---- This is your answer
Hope this helps!